Canasta básica de alimentos real en hogares beneficiarios de la Fundación Ximena Rico Llano de Medellín-Colombia (2010)
ABSTRACT: To determine in the households receiving benefits from Ximena Rico Llano foundation Medellin-Colombia, the composition of consumed food, what foods these families use to buy and the cost for no nutritious food. Materials and methods: Cross sectional study. Randomized and representative sample of 91 families from the foundation were selected. An structured survey was applied to define the basic foods consumed according the accessibility and to determine what type and how much food families buy, and also the cost, calories and proteins content of these foods. Moreover the cost and the accessibility for no nutritious food were also identified. Results: the basic meals consumed for families were represented for 30 aliments distributed in 12 groups; however, 16% of the families didn’t have access to staple food like meat, legumes, dairy products, fruits and vegetables. The cost of the basic food was about $448.623 (US$216), it was the equivalent to 1,03 basic wage. The cost for no nutritious food represented 14% of the total Money spending in food per month. Conclusions: The basic foods of the families from Ximena Rico Llano Foundation consisted of 30 aliments, and no variety was observed. These families didn’t meet the nutritional requirements. Acquisition of products different to food represented another important investments that restrain families to spent more in staple food.